Penguatan Pengetahuan Nutrisi Lokal untuk Pemberian MPASI dalam Pencegahan Faltering Growth pada Balita - Lusiana, Ika; Apriani, Lia Arian (CV Putra Publisher, 2025)
Faltering growth is characterized by slow weight gain in early childhood, often the root cause of stunting in developing countries. In Indonesia, the stunting rate in toddlers reaches 24%, with high prevalence also recorded in West Nusa Tenggara (NTB). The leading causes of stunted growth include inadequate nutritional intake and infection, which impact children's physical and cognitive development. Early intervention through nutrition education is essential to prevent long-term impacts. Through education and leaflet media, this community service program aims to improve mothers' knowledge about locally-based MPASI at the Pringgarata Health Center. This program takes place in three stages—preparation, implementation, and evaluation—with 20 participants consisting of mothers and community leaders. The evaluation results showed a significant increase in mothers' knowledge from 30% to 85% after education, stating that this approach effectively improves understanding and potentially prevents faltering growth.